DEVELOPING STORY JUMPER-BASED TEACHING MEDIA TO ENRICH KINDERGARTEN STUDENTS’ VOCABULARY - Rameswara, Ketut Hari; Adnyani, Luh Diah Surya; Pratiwi, Ni Putu Astiti (Universitas Pendidikan Ganesha, 2019)
The demand of integrating technology in instruction is essential since today’s learning became Education 4.0. Thus, teachers are in need of help in creating suitable media to be implemented. This research aimed to know the development of story jumper to enrich kindergarten students’ vocabulary and to know its quality. This research was Design and Development Research implementing ADDIE model. The subject of this research were three teachers and three kindergarten students. To know the quality, classroom observation, post-implementation questionnaire, and an interview were administered. The result showed, the media are good in helping the teachers deliver the material, and it is very easy to use. The students admitted that the media were able to attract their attention. The media produced are good enough to be used in further implementation. Teachers could refer to Story Jumper because of its practicality and benefits in helping them achieving the learning outcomes.